2011
DOI: 10.1002/lary.22150
|View full text |Cite
|
Sign up to set email alerts
|

Tympanic membrane wound healing in rats assessed by transcriptome profiling

Abstract: The findings of this study provide a baseline against which to identify disease-related molecular signatures, biomarkers, and to develop new treatments for TM conditions based on molecular evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Also Santa Maria et al [12,27] using the whole rat genome arrays observed increased expression of Hbegf gene. They also observed up-regulation of other growth factors such as: FGF7 (KGF1), FGF2 (bFGF) 12 h after injury [12,28], in the time point that was not included in our study. Ishibashi et al [29,30] also studied the expression of growth factors mRNA during healing of TM perforations using RT-PCR method and found that KGF and TGFa m RNA were induced rapidly, peaking 3 days after wounding and then declining.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Also Santa Maria et al [12,27] using the whole rat genome arrays observed increased expression of Hbegf gene. They also observed up-regulation of other growth factors such as: FGF7 (KGF1), FGF2 (bFGF) 12 h after injury [12,28], in the time point that was not included in our study. Ishibashi et al [29,30] also studied the expression of growth factors mRNA during healing of TM perforations using RT-PCR method and found that KGF and TGFa m RNA were induced rapidly, peaking 3 days after wounding and then declining.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested to be the predominant growth factor in the epithelialization by accelerating keratinocyte migration [26]. Also Santa Maria et al [12,27] using the whole rat genome arrays observed increased expression of Hbegf gene. They also observed up-regulation of other growth factors such as: FGF7 (KGF1), FGF2 (bFGF) 12 h after injury [12,28], in the time point that was not included in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The literature data concerning the expression of VEGF m RNA in the course of TM healing are inconsistent. In a study of TM wound healing in rats assessed by transcriptome profiling, VEGF was up-regulated at 12 h after injury [13]. The differences in mRNA expression observed in various studies may result from differences in methodological paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in TM and skin healing suggest that also growth factors may be expressed differently and that the experience derived from the repair of other tissues may not be fully applicable to TM. Most of the information concerning the role of various biomolecules involved in the coordination of TM healing comes from the research on gene expression [12,13]. Our preliminary study performed using Rat Wound Healing RT 2 Profiler PCR Array showed increased levels of mRNA for hepatocyte (HGF) and vascular endothelial growth factor (VEGFa), mainly in the proliferative stage of the TM healing process [12].…”
Section: Introductionmentioning
confidence: 96%